구강내 악성흑색종에 대한 임상연구 - 김욱규(Uk-Kyu Kim); 허진호(Jin-Ho Heo); 황대석(Dae-Seok Hwang); 김용덕(Yong-Deok Kim); 신상훈(Sang-Hun Shin); 김종렬(Jong-Ryoul Kim); 정인교(In-Kyo Chung) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2008)
The prognosis of oral malignant melanoma is poor compared with cutaneous melanoma. It may be related to the difficulty of wide enough resection, the early hematogenous matastases, higher stage at initial diagnosis, and tendency to growth vertically. In the view of histological differences between oral mucosa and skin, it is impossible use Clark’s and Breslow’s classifications for prognosis. The great problem is that there is still no consensus on the treatment due to rarity . Because data collection from case reports is considered to be the best source of information and should be pooled to analyze key determinants of outcome, We analysed 6 cases of primary malignant melanoma of the oral cavity which were diagnosed and treated in Pusan National University Hospital on recent 7 years and reviewed the literatures. Immunohistochemical study on S 100 Protein, GP 100 (HMB-45) with biopsy was usable to confirm the melanoma. Three patients who were treated by surgery, chemotherapy are alive, but a patients who couldn’t received benefit care surgically due to poor condition was died of distant metastasis, and two patients who refused to surgery are still alive. Neck dissection including wide excision is recommended if lymph node involvement is suspected. Additionally, adjuvant chemotherapy could be considered as supporting therapy for malignant melanoma. KCI Citation Count: 1